Respon Nahdlatul Ulama (NU) terhadap Wahabisme dan Implikasinya bagi Deradikalisasi Pendidikan Islam - Shidqi, Ahmad (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
The rise of Islamic radicalism action that is more expansive in Indonesia because of Wahhabism actions. This group often “mengkafirkan” “mensyirikkan”, “membid’ahkan” other groups of Muslim. The actions may grow Islamic radicalism. “NU” that is as one of other groups of Muslims who faithfully practice the number of religious rites such as “tahlil”, “ziarah kubur” (pilgrimage to grave), “maulid”, is often made as the target of this Wahhabi. Therefore, a number of people from both structural and cultural of “NU” have done the consolidation to response the expansion of Wahhabism.